In-Vitro Chromium Bioremediation Potential Using Bacteria Consortium from Chromium Polluted Soil - Vinno Bayu Christofan; Wahyu Surakusumah; Peristiwati Peristiwati (School of Postgraduate Studies, Diponegoro Univer, 2026)
This research aims to obtain an adequate formulation of bacterial consortium for chromium waste management, where the bacteria Bacillus sp., Bacillus licheniformis and Bacillus anthracis obtained from the chromium polluted environment have the potential as bioremediation agent of chromium waste. The use of bioremediation is considered to be effective and efficient in waste management and has become the solution to cleanse the environment from pollution without excessive use of chemical substances. The methods used in this research are quantitative methods with an experimental approach. Sample isolated from soils and then selected based on their resistance toward chromium stress, the sample then identified using biochemical and molecular method, after that the sample chromium content is tested in the beginning of the observation until the end of observation at the 12th hour. This research shows that the bacterial consortia of Bacillus sp. and Bacillus anthracis have the best synergy that is marked by the growth of streak colonies that are clearly seen. In the chromium reduction test, the Bacillus sp. and Bacillus anthracis consortia have the highest chromium reduction percentage, reaching 26% meanwhile the percentage of Bacillus licheniformis and Bacillus anthracis consortia have the reduction percentage of 9.4% marked as the lowest out of all the tested consortia. The conclusion of this research is the consortia of Bacillus sp. and Bacillus anthracis is the best consortia in chromium reduction property out of all consortia that is tested in this research, this shows that the Bacillus sp. and Bacillus anthracis consortia as the highest potential consortia to be applied in chromium waste bioremediation systems.